A new intermetallic phase formation in MgSiNi magnesium-based in-situ formed alloys. (June 2019) - Barri, Nima; Salasel, Amir Reza; Abbasi, Alireza; Mirzadeh, Hamed; Emamy, Massoud; Malekan, Mehdi
Abstract: The effects of nickel addition on the microstructure and phase formation in the magnesium-silicon alloy were studied. Besides the primary and eutectic in-situ formed Mg2 Si phase in the MgSi alloys, a new intermetallic phase was identified in the Ni-containing alloys. Based on energy-dispersive spectroscopy (EDS) and X-ray diffraction analyses, it was shown that this phase contains Mg, Ni, and Si elements, which contradicts the presence of the expected Mg2 Ni phase. Through rigorous EDS analysis, the new in-situ formed phase was identified as (Mg, Ni)3 Si or more accurately as Mg8 Ni7 Si5 intermetallic compound, called χ-phase, which has not been reported so far in the MgSiNi ternary space. Finally, the properties of the studied MgSiNi alloys were also briefly discussed. Highlights: Effect of Ni on microstructure and phase formation in the MgSi alloy was studied. New intermetallic compound called χ-phase was found in the MgSiNi ternary space. Hot extrusion process resulted in remarkable enhancement of mechanical properties.